2018
DOI: 10.1093/brain/awy220
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective exendin-4 enhances hypothermia therapy in a model of hypoxic-ischaemic encephalopathy

Abstract: Hypoxic-ischaemic encephalopathy (HIE) causes 25% of neonatal deaths worldwide. Rocha-Ferreira et al. demonstrate that a diabetes drug protects the neonatal brain in a model of acute HIE, and confirm that the required receptor is found in human perinatal brain tissue. Synergistic combination with clinical hypothermia enhances therapy, supporting potential translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 77 publications
3
58
0
1
Order By: Relevance
“…Exendin-4 is an analog of the human glucagon-like peptide-1 (GLP-1) gut hormone peptide. In a study by Rocha-Ferreira et al (2018), exendin-4 was found to enhance the neuroprotection of therapeutic hypothermia. The combined therapy with human urinary kallidinogenase (HUK) and hypothermia enhanced the efficiency by promoting angiogenesis and regeneration and rescuing tight-junction loss in HIE rat model (Gao et al, 2018).…”
Section: Hypothermia Combined With Other Neuroprotective Methodsmentioning
confidence: 99%
“…Exendin-4 is an analog of the human glucagon-like peptide-1 (GLP-1) gut hormone peptide. In a study by Rocha-Ferreira et al (2018), exendin-4 was found to enhance the neuroprotection of therapeutic hypothermia. The combined therapy with human urinary kallidinogenase (HUK) and hypothermia enhanced the efficiency by promoting angiogenesis and regeneration and rescuing tight-junction loss in HIE rat model (Gao et al, 2018).…”
Section: Hypothermia Combined With Other Neuroprotective Methodsmentioning
confidence: 99%
“…Therefore, the normal advantages of rapidly repurposing drugs at a lower cost than the drug development process (Ayoub et al, 2018;Mousa and Ayoub, 2019) may be diminished for application to HIE. Potential safety risks could be reduced since the administration of the drug would likely only be required during a short acute period following the HI insult over a 48 h period (Rocha-Ferreira et al, 2018). However, depending on the diabetes drug in question, an important consideration is the potential to induce a hypoglycaemic effects when perturbations in glucose metabolism (hypoglycaemia and hyperglycemia) are already common in newborn infants with HIE (Vannucci, 1992;Salhab et al, 2004;Basu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Exendin-4, liraglutide and quinoxaline 6,7-dichloro-2-methylsulfonyl-3-N-tert-butylaminoquinoxaline (DMB, an agonist and allosteric modulator of the GLP-1R) have been shown to increase neuron survival under OGD in vitro by reducing reactive oxygen species (ROS), apoptotic and necrotic mechanisms Zhang et al, 2016;Zhu et al, 2016). The potential that GLP1-R agonists have for treating perinatal HIE has been further strengthened in two recent studies demonstrating: (1) that exendin-4 has significant therapeutic efficacy in the mouse model of neonatal HIE (Rocha-Ferreira et al, 2018), (2) and that liraglutide exerts neuroprotection via the PI3k/Akt pathway (Zeng et al, 2020). The study by Rocha-Ferreira and colleagues demonstrated that systemic administration either directly after HI injury, or even 2 h later significantly reduced the size of the brain infarct, the inflammatory response and the oxidative stress.…”
Section: Incretin / Glp1-receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…One such drug, exendin-4 (EX-4), a glucagon-like peptide-1 (GLP-1) receptor agonist, currently in clinical use for type II diabetes, has demonstrated neuroprotective effects in several animal models of PD (Bertilsson et al, 2008; Harkavyi et al, 2008; Kim et al, 2009, 2017; Li et al, 2009; Cao et al, 2016; Chen et al, 2018; Yun et al, 2018). These data, together with its excellent safety profile (Bertilsson et al, 2008; Harkavyi et al, 2008; Kim et al, 2009; Li et al, 2009; MacConell et al, 2015; Cao et al, 2016; Yun et al, 2018), even at high doses (Rocha-Ferreira et al, 2018) and its ability to pass the blood brain barrier (Kastin and Akerstrom, 2003; Athauda et al, 2017a; Zanotto et al, 2017), supported its use in clinical trials in patients with PD (Aviles-Olmos et al, 2013, 2014; Athauda et al, 2017a). Patients that received EX-4 showed improvements in motor symptoms, cognition, depression and sleep quality compared with patients treated with conventional PD medication (Aviles-Olmos et al, 2013, 2014).…”
Section: Introductionmentioning
confidence: 86%